Working conditions, health status, and musculoskeletal disorders among hospital cleaning workers: a cross-sectional study in Turkey - Volkan Medeni; İrem Medeni; Müberra Erkaya Tosun; Asiye Uğraş Dikmen; Mustafa Necmi İlhan (Medycyna Pracy)
Background Cleaning workers face many workplace risk factors and may experience many health problems. In this context, this study aimed to evaluate the musculoskeletal disorders, the health status of hospital cleaning workers, and the working conditions and risk factors affecting the workplace environment.